Anticonvulsant effects of thymoquinone, the major component of Nigella sativa seeds in mice - S Parvardeh; M Fatehi; H Hosseinzadeh (Institue of Medicinal Plants, ACECR, 2003)
The anticonvulsant effect of thymoquinone, the major component of nigella sativa seeds, were investigated using pentylenetetrazole (PTZ) and Maximal electroshock test (MES), as petit mal and grand mal epilepsy models in mice, respectively. In PTZ- induced convulsion, the intraperitoneally injection of thymoquinone with doses of 40 and 80 mg/kg, prolonged the onset of seizures the duration of clonic seizures. The protection activity of thymoquinone againt mortality was 71.4% and 100% in the mentioned doses, respectively. In MES, thymoquinone faild to reduce the duration of convulsion, whereas exhibited a complete protection against mortality. In PTZ test, flumazenil (10 mg/kg ip), an antagonist of benzodiazepine site, inhibited the prolongation of convulsion latency, but did not show any effect on the duration of clonic seizures. In PTZ test, the ED50 of diazepam was obtained 1.13 mg/kg (95% CL: 0.89- 1.44). These results indicate that thmoquinone may have anticonvulsant activity in petit mal epilepsy. Moreover, it may exhibits an nticonvulsant activity, at least in parts, through benzodiazepine receptors.